Formulation and Evaluation of Pralidoxime-PLGA Microspheres as Antidote against Organophosphorous Poisioning (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The objective of the present work is to formulate and evaluate Pralidoxime chloride (PAM)-controlled release microspheres using poly (lactic-co-glycolic acid) (PLGA, 50: 50) as polymer and poly vinyl alcohol as surfactant. Materials and Methods: PAM-controlled release microspheres were prepared by solvent evaporation method. The prepared microspheres were characterized by flow properties such as angle of repose, compressibility index, particle size, and encapsulation efficiency and drug release profiles. Results: All the prepared microsphere were spherical and exhibited good flow properties. PAM was greatly encapsulated with PLGA and poly vinyl alcohol. The Fourier transform infrared spectroscopy and differential scanning calorimetry studies were conducted for pure drug, polymer, and optimized formulations, the studies revealed that they were no incompatibilities between drug and polymers used in the present study. Scanning electron microscopy analysis showed that the microspheres were uniform and spherical in nature with good surface characteristics among all the PAM-controlled release microspheres formulations. Conclusions: The optimized formulation (F 6) prepared with appropriate proportion of polymer PLGA and surfactant poly vinyl alcohol was found to extend the release of drug up to 28 h.